A Fully-Integrated Wireless System for Intracranial Direct Cortical Stimulation, Real-Time Electrocorticography Data Trasmission and Smart Cage for Wireless Battery Recharge - Marco ePiangerelli; Marco eCiavarro; Antonino eParis; Stefano eMarchetti; Paolo eCristiani; Cosimo ePuttilli; Napoleon eTorres; Alim Louis Benabid; Pantaleo eRomanelli (Frontiers in Neurology, 2014)
Wireless transmission of cortical signals is an essential step to improve the safety of epilepsy procedures requiring seizure focus localization and to provide chronic recording of brain activity for Brain Computer Interface(BCI) applications .Our group developed a fully implantable and externally rechargeable device, able to provide wireless electrocorticographic (ECoG) recording and cortical stimulation (CS). The first prototype of a wireless multi-channel very low power ECoG system was custom-designed to be implanted on non-human primates. The device,named ECOGIW-16E, is housed in a compact hermetically sealed Polyether ether ketone (PEEK) enclosure, allowing seamless battery recharge. ECOGIW-16E is recharged in a wireless fashion using a special cage designed to facilitate the recharge process in monkeys and , developed in accordance with guidelines for accommodation of animals by Council of Europe (ETS123). The inductively recharging cage is made of nylon and provides a thoroughly novel experimental setting on freely moving animals. The combination of wireless cable-free ECoG and external seamless battery recharge solve the problems and shortcomings caused by the presence of cables leaving the skull,providing a safer and easier way to monitor patients and to perform ECoG recording on primates. Data transmission exploits the newly available Medical Implant Communication Service band (MICS: 402-405 MHz). ECOGW-16E was implanted over the left sensorimotor cortex of a macaca fascicularis to assess the feasibility of wireless ECoG monitoring and brain mapping through CS. With this device we were able to record the everyday life ECoG signal from a monkey and to deliver focal brain stimulation with movement elicitation.